2011
DOI: 10.1103/physrevlett.107.238701
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects in the Growth of Networks

Abstract: We show that to explain the growth of the citation network by preferential attachment (PA), one has to accept that individual nodes exhibit heterogeneous fitness values that decay with time. While previous PAbased models assumed either heterogeneity or decay in isolation, we propose a simple analytically treatable model that combines these two factors. Depending on the input assumptions, the resulting degree distribution shows an exponential, log-normal or power-law decay, which makes the model an apt candidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
209
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(214 citation statements)
references
References 22 publications
4
209
1
Order By: Relevance
“…The typical approach is to study the evolution of the number of citations received by a paper in a given time frame (usually one year), since its publication. The nature of the decay has been controversial, between claims of an exponential trend (Avramescu, 1979;Nakamoto, 1988;Medo et al, 2011) and analyses supporting a slower power law curve (Pollman, 2000;Redner, 2005;Bouabid, 2011;Bouabid and Larivière, 2013). This is partly due to the different types of analysis and the use of distinct data sources.…”
Section: Introductionmentioning
confidence: 99%
“…The typical approach is to study the evolution of the number of citations received by a paper in a given time frame (usually one year), since its publication. The nature of the decay has been controversial, between claims of an exponential trend (Avramescu, 1979;Nakamoto, 1988;Medo et al, 2011) and analyses supporting a slower power law curve (Pollman, 2000;Redner, 2005;Bouabid, 2011;Bouabid and Larivière, 2013). This is partly due to the different types of analysis and the use of distinct data sources.…”
Section: Introductionmentioning
confidence: 99%
“…There are likely other economic systems that would benefit from temporal network modeling. Networks that, like citation networks [105] are normally thought of as strictly growing, could show temporal effects in the growth that could benefit from being studied in a temporal-network framework.…”
Section: Other Systemsmentioning
confidence: 99%
“…In this work, we use a model that extends the one suggested in [20]. The system is composed of researchers (or authors) and papers, indicated by Latin and Greek letters, respectively.…”
Section: Model and Artificial Datamentioning
confidence: 99%
“…In particular, we extend a previous model constrained on the citation dynamics of scientific papers [20] by assuming that researchers are endowed with intrinsic productivity and ability levels-the latter determining the fitness of their authored papers-that in turn make connections to the existing body of literature according to the modified preferential attachment mechanism described above. The artificial bibliometric data generated by the model then allow us to compute a variety of impact indicators, which can be compared with the individual traits of researchers in order to determine what these indicators actually capture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation